Toward an integrated model of dietary behavior: Social determinants and adherence to the mediterranean diet - Francesca Romana Lenzi; Ciro Clemente De Falco; Michela Cavagnuolo; Vincenzo Esposito; Ferdinando Iazzetta (PLoS ONE, 2025)
Background Adherence to the Mediterranean diet is widely recognized as a protective factor for health, yet its determinants remain complex and multidimensional. This study investigates the social, economic, cultural, familial, and perceptual factors associated with adherence to the Mediterranean diet within the Italian population. Methods Using a stepwise approach based on four linear multiple regression models, we analyzed nationally representative survey data to assess how different sets of variables influence adherence to the Mediterranean diet. The analysis was informed by the theoretical framework of the social determinants of health, the nutrition transition theory, and Bourdieu’s concept of cultural capital. Results Initial models identified younger age and higher educational attainment as significant predictors of greater adherence. With the inclusion of socioeconomic variables, household income emerged as a more robust predictor, while the effect of education diminished. Subsequent models showed that family cultural capital and individual awareness of diet-health relationships significantly increased explanatory power. In the final model, perceptual and cognitive variables—especially the recognition of the role of nutrition and body weight in health—were among the strongest predictors (adjusted R² = 0.25; Durbin-Watson = 1.98). Conclusions Adherence to the Mediterranean diet reflects not only economic or educational resources, but also deeper cultural and cognitive dimensions. The findings suggest that effective public health interventions should integrate nutritional education, cultural engagement, and targeted support for socially and geographically disadvantaged groups. Rather than a purely behavioral choice, dietary adherence should be understood as a socially structured practice embedded in broader patterns of inequality.